Assessment of performance and impact of irrigation and water resources systems in Taiwan and Sri Lanka - Sakthivadivel, Ramaswamy; Aloysius, Noel; Matsuno, Y. (International Water Management Institute, 2001)
This report is based on the Taiwan's irrigation systems.The first part of this report gives a brief introduction to the Taiwan irrigation systems. Based on the visit and discussions by two IWMI staff members from 25 September to 4 October 2000 with the Association Managers, staff of the Agricultural Engineering Research Centre (AERC) and staff of the Council of Agriculture (COA), certain issues were identified in the two systems, which are detailed. In the second part, the results of analyses of the performance of these two irrgation systems of Taiwan are compared with a irrgation system from Sri Lanka.